المسؤولية الجنائية عن نقل الأمراض المعدية للغير: فيروس كورونا المستجد ومتحوراته نموذجا: دراسة مقارنة - عبدالرازق، رانا مصباح عبدالمحسن (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2022)
هدفت هذه الدراسة إلى بيان أحكام المسؤولية الجنائية الناشئة عن نقل الأمراض المعدية للغير، وبالأخص نقل وباء فيروس كورونا المستجد ومتحوراته من الشخص المريض سواء كان ذلك عن قصد أو بسبب عدم اتخاذ الاحتياطات والتدابير اللازمة لوقاية نفسه أولا، ومن ثم وقاية غيره من العدوى. وعلى الرغم من أن دول العالم عامة والمملكة العربية السعودية على وجه الخصوص قامت باتخاذ الإجراءات الاحترازية والوقائية لمواجهة هذا الوباء والحد منه بقدر المستطاع حماية لمواطنيها، إلا أن هذه الإجراءات الوقائية لم تكن كافية للحد من انتقال هذا المرض، وهو ما استدعى مواجهة هذه الجائحة تشريعيا نظرا للأضرار التي ألحقتها بالدول والأفراد على السواء، وذلك بتحديد المسؤولية الجنائية المترتبة على تعمد نقل المصاب هذا الفيروس إلى الغير واستخدام مرضه كسلاح ضد المجتمع، وما يترتب على فعله هذا من نتيجة جرمية تضر بسلامة الغير وصحته مما قد تؤدي لإيذائه أو حتى وفاته. واعتمدت الدراسة على استخدام المنهج الوصفي التحليلي بالإضافة إلى الاستعانة بالمنهج المقارن، واشتملت هذه الدراسة على ثلاثة مباحث: تناولت بيان ماهية فيروس كورونا المستجد، وكيفية انتقاله، وأعراض الإصابة به، والتدابير الوقائية لمنع الإصابة به وانتشاره، والتعرف على أركان جريمة نقل العدوى بفيروس كورونا المستجد للغير سواء كان عمدا أو بطريق الإهمال، وأحكام العقاب. وقد توصلت الدراسة للعديد من توصيات التي ساهمت في الحد من انتشار فيروس كورونا المستجد ومكافحته. This study aimed to clarify the provisions of criminal responsibility arising from the transmission of infectious diseases to others, in particular the transmission of the new epidemic of the Corona virus and its variants from the sick person, whether that was intentionally or because of not taking the necessary precautions and measures to protect himself first, and then to prevent others from infection. Although the countries of the world in general and the Kingdom of Saudi Arabia in particular have taken precautionary and preventive measures to confront this epidemic and reduce it as much as possible to protect their citizens, these preventive measures were not sufficient to limit the transmission of this disease, which necessitated confronting this pandemic legislatively, given For the damage it has caused to countries and individuals alike, by determining the criminal responsibility resulting from the deliberate transmission of the infected person with this virus to others and the use of his disease as a weapon against society, and the criminal consequences of doing so that harm the safety and health of others, which may lead to his injury or even his death. The study relied on the use of the descriptive analytical method in addition to the use of the comparative method, and this study included three sections: it dealt with a statement of the nature of the emerging corona virus, how it is transmitted, symptoms of infection with it, preventive measures to prevent infection and its spread, and identifying the pillars of the crime of transmission of infection with the emerging corona virus. To others, whether intentionally or by negligence, and the provisions of punishment. The study reached many recommendations that contributed to limiting and combating the spread of the emerging corona virus.
Keywords: فيروس كورونا "كوفيد-19" -- نقل العدوى -- القانون الجنائي -- السعودية